(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
In recent years, the efficiency of supercomputer centers, energy consumption, and the resolution of coordination issues have gained increasing relevance, leading to the emergence of sector-specific requirements such as architectural design, human resources management, computational models, information management systems, and administrative governance. This article analyzes the historical development of supercomputers, the actors, infrastructure, and operational components of supercomputer centers, taking into account the challenges that affect their efficiency. The study concludes that effective coordination and management among the stakeholders of a supercomputer center play a crucial role in ensuring efficient and sustainable operations. Based on the findings, the paper proposes recommendations for organizing the efficient functioning of such centers. Keywords: Supercomputer, Digital Economy, Data Center, Governance, Efficiency, Virtual Workspace.